High-resolution record of the Late Saalian–Eemian environmental changes in the northeastern White Sea Region (Bychye section) inferred from benthic foraminifers - Ovsepyan , Yaroslav; Taldenkova , Ekaterina; Bauch, Henning A.; Rudenko , Olga; Stepanova , Anna (2011)
Paleoenvironmental history of the White Sea region during the late Saalian–Eemian transition is reconstructed on the basis of the high-resolution record of benthic foraminifers from a 4.5 m thick marine sediment sequence directly overlying Saalian till in the Bychye section on the Pyoza River, NE White Sea Region. Besides benthic foraminifers which are the most abundant microfossil group in the studied section, also ostracods, pollen, aquatic palynomorphs as well as lithology and benthic foraminiferal stable isotope composition (δ18O, δ13C) were investigated. Palynological correlation with the previously studied sections confirms the age estimation from c. 133 to 120 ka (Devyatova, 1982; Grøsfjeld et al., 2006). Paleoecological analysis of foraminiferal assemblages is based on ecological preferences of different benthic species distinguished in modern Barents and Kara seas (Polyak et al., 2002, Korsun et al., 1994) supported by factor analysis. Five Ecozones were established which reflect rapid postglacial flooding of the territory after the disappearance of the Saalian ice sheet and consequent shallowing of the sea basin likely due to glacial rebound. Ecozone 1 corresponds to the earliest stage of inundation. Composition of microfossils suggests with the predominance of the arctic opportunistic species Elphidium clavatum among foraminifers suggests it was a cold Arctic coastal environment probably with turbid waters, high sedimentation rates and heavy seasonal sea-ice cover. Relative deepening of the shelf basin continued in Ecozone 2 as suggested by the high percentage of river-distal foraminifers indicating bottom water salinities above 30 and less heavy seasonal sea-ice cover. Foraminiferal assemblages are very similar to those occurring in the mid-shelf regions of the Laptev and Kara seas. The maximum flooding and deepening of the basin registered in Ecozone 3 as indicated by the highest percentage of the relatively deep-water species Melonis barleeanus. According to palynological composition, Ecozone 3 ...